Comparison of antimicrobial efficacy of (between) 0.2% chlorhexidine and herbal mouthwash on salivary Streptococcus mutans: A randomized controlled pilot study - Swara Shah; Seema Bargale; Bhavna H Dave; Anshula Deshpande; Pratik B Kariya; Anuradha Karri (Wolters Kluwer Medknow Publications, 2018)
Background: The chemomechanical plaque control measures are helpful in controlling dental plaque and thus caries, especially in pediatric age group. Aim: This study aims to compare effectiveness of herbal mouthrinse containing Terminalia chebula to that of 0.2% chlorhexidine against children's salivary mutans streptococci levels. Settings and Design: A double-blind, randomized, controlled study design will be framed for conducting this study. Methods: A total of 45 participants were randomly categorized in Group 1, Group 2, or Group 3 (control group, experimental group, or negative control). Baseline unstimulated saliva was collected. All the participants were instructed regarding the use of mouthrinse for 2 weeks. After 2 weeks, again unstimulated saliva was collected. After collection, saliva samples were sent for microbiological analysis. Statistical Analysis: The mean colony-forming units (CFU/ml) were determined. Paired t-test, ANOVA test, and post hoc test were applied for statistical analysis. Results: Statistically significant difference in CFU count has been observed in 0.2% chlorhexidine and Oratreat groups at 15 days as compared to baseline (P < 0.001). At 15 days, reduction in CFU count has seen more in Oratreat group as compared to 0.2% chlorhexidine group, and the difference is statistically significant (P < 0.001). Conclusion: 0.2% chlorhexidine and Oratreat mouthwash reduce the salivary Streptococcus mutans count. Oratreat herbal mouthwash has proved to be better as compared to 0.2% chlorhexidine mouthwash.